Relasi Pendidikan Islam, Politik dan Kekuasaan - Annisa Tusadia; Qolbi Khoiri (Journal on Education, 2023)
Discovering the connections between Islamic education, politics, and electricity is the goal of this essay. For analysis and conclusion, this research approach uses library or literature studies. The author employs literature observation to gather information, specifically research done using information related to the family members of Islamic education, politics and energy, the internet, books, and other pertinent resources. The results of this observation are: There is a strong connection between electricity politics and the realm of Islamic education. The seriousness with which the ulama and umara have listened to educational issues in order to support groups and their supporters' sociopolitical positions has left its mark on Islamic culture. It is undeniable that the rulers actively promote the advancement of Islamic education, and the rulers depend on the support of educational institutions to maintain their hold on power. Why is that? Because Islamic government's goal is to defend truth and justice, which cannot be accomplished without applying Shari'a.